Illicit Substance use among adolescents and youths in Zimbabwe: a stakeholder’s perspective on the enabling factors and potential strategies to address this scourge - Dzinamarira, Thulani Runyararo; Mutevere, Mirriam; Nyoka, Stephen; Moyo, Enos; Mkwapatira, McAuthur; Murewanhema, Grant; Dzinamarira, Tafadzwa (International Journal Of Community Medicine And Public Health, 2023)
Drug and illicit substance use among adolescents and the youth is a rising global health concern. In Zimbabwe, this problem has also been increasing in magnitude, with reports indicating that the COVID-19 pandemic accelerated the growth of the problem. Decisively dealing with the problem requires an understanding of the contributory factors from all significant stakeholders’ perspective. We qualitatively explored the contributory factors to drug and substance use among the adolescents and youths in Zimbabwe from a significant stakeholders’ perspective. We conducted three focus group discussions with relevant stakeholders to reach saturation point. Four themes emerged on enabling factors, namely idleness among the youths and the adolescents, increased access to illicit substances, low community awareness of the signs of drug and substance use leading to delayed identification, and absence of social workers in the communities. Four themes emerged as possible strategies to curb drug and illicit substance use in this age group, namely capacitation of mental health institutions, expanding community awareness programmes, tailored approaches for adolescent and youth programming, and strengthening law enforcement. A convergence with these relevant stakeholders is urgently needed to map strategies to deal with the enabling factors place, and to strengthen strategies to curb the problem.